PECULIARITIES OF THE FUNCTIONAL ACTIVITY OF BLOOD EOSINOPHIL GRANULOCYTES IN PULMONARY TUBERCULOSIS - Yu. V. Kolobovnikova; O. I. Urazova; V. V. Novitskiy (Бюллетень сибирской медицины)
Eosinophils are polyfunctional leukocytes detected in excess in blood and in the focus of granulomatous inflammation in pulmonary TB.The research objective was to evaluate the adhesive properties as well as cytokine-secretory and antibacterial activity of blood eosinophils in pulmonary TB.The research has been conducted on eosinophils isolated from peripheral blood of 43 patients with freshly identified progressive destructive TB with and without eosinophilia. Using flow cytometry and ELISA, expression of CD9 and CD18 adhesion molecules on blood eosinophils has been studied along with the phagocyte and cytokine-secretory functions and activity of eosinophil granulocyte peroxidase.As a result of the research it has been established that in TB patients with eosinophilia the number of CD18-expressing eosinophils rises, whereas the amount of CD9+ remains within norm. Activation of the phagocyte function of blood eosinophil granulocytes is associated with the decrease in eosinophil peroxidase activity, while the increase in IL-5 and TNFα secretory reactivity is connected with oppositely directed changes in  IL-2 basal secretion by eosinophils in vitro (a fall in infiltrative TB and a rise in disseminated TB).